Credit Advertising and the Law: Truth in Lending and Related Matters - Gerald J. Thain (Washington University Law Quarterly, 1976)
Whether full disclosure of credit terms will in fact improve the bargaining power of credit consumers is debatable. Borrowers may not be sophisticated enough to make effective use of the information disclosed and may not, in fact, have a choice of lenders. Furthermore, an applicant with a precarious credit status may care much less about locating favorable credit terms than about obtaining any credit. For these reasons, critics often decry Congress’ most recent legislation on credit advertising, the Truth-in-Lending Act, as “middle-class legislation.” Although categorized as “consumer protection legislation,” the Act offers little assistance to the consumers most in need of protection—those who have trouble obtaining credit on any terms.
Keywords: Advertising; Consumer protection; Credit